Managing Uncertainty: Physicians' Decision Making for Stroke Prevention for Patients with Atrial Fibrillation and Intracerebral Hemorrhage - Ivany, Elena; Lotto, Robyn R.; Lip, Gregory Y.H.; Lane, Deirdre A. (Thrombosis and Haemostasis, 2022)
Background Stroke prevention in patients with atrial fibrillation (AF) post-intracerebral hemorrhage (ICH) is an area of clinical equipoise. Little is known about the tools and processes that physicians use to make decisions regarding anticoagulation in this high-risk patient population.Objective To explore physicians' decision-making process regarding stroke prevention in patients with AF and a recent history of ICH.Methods Qualitative study, utilizing semistructured interviews and analyzed using Framework analysis.Results Twenty physicians from five European countries (Austria, France, Germany, Spain, United Kingdom) participated. The overarching theme “Managing uncertainty,” addressed the process of making high-risk clinical decisions in the context of little available robust clinical evidence for best practice. Three subthemes were identified under the umbrella theme: (1) “Computing the risks,” captured the challenge of balancing the risks of ischemic stroke with the risk of recurrent ICH in a complex patient population; (2) “Patient factors” highlighted the influence that physician-perceived patients' beliefs and previous experience of stroke had on physicians' decisions; and (3) “Making a decision” explored the process of reaching a final decision regarding initiation of OAC therapy or not.Conclusion Physicians described the process of deciding on stroke prevention in patients with AF post-ICH as “challenging” due to considerable “clinical equipoise.” Key factors that affected decision making were patient comorbidities, functional status, and patient willingness to engage with OAC therapy. Shared decision making was believed to be beneficial, but physicians believed that the ultimate responsibility to decide on stroke prevention lay with the clinician.
Keywords: stroke prevention; intracerebral hemorrhage; management; atrial fibrillation